Membingkai Kisah Syafaat Abraham dari Perspektif Spritualitas Pentakostal - Manurung, Kosma (Institut Agama Kristen Negeri Palangka Raya, 2023)
Not everyone can write down his life story but the Bible gives a special place to the story of Abraham's life to be passed on to today's believers. The story of Abraham's intercession for the cities of Sodom and Gomorrah in Genesis 18:16-33 is an interesting story to study. It is said that God had determined to destroy the inhabitants of Sodom and Gomorrah, but Abraham tried to negotiate with God so that if possible God would keep His punishment against the cities of Sodom and Gomorrah. However, in reality the only survivors of this tragedy were Lot and his two daughters. This research intends to frame the story of Abraham's intercession from the perspective of Pentecostal spirituality. By using the method of narrative interpretation and literature review, it is hoped that it will provide a clear overview of the life lived by Abraham, provide a strong meaning about Abraham's intercession, and frame it from the perspective of Pentecostal spirituality. In conclusion, the Pentecostals view that the story of Abraham's intercession is a story of perseverance in faith, the courage to act out of compassion for others, and is a picture of the mission of the church empowered by the Holy Spirit. Tidak semua orang bisa menuliskan kisah hidupnya namun Alkitab memberikan tempat khusus pada kisah kehidupan yang dijalani oleh Abraham untuk diwariskan pada orang percaya masa kini. Kisah syafaat Abraham untuk kota Sodom dan Gomora di Kejadian 18: 16-33 adalah kisah yang menarik untuk dikaji. Diceritakan bahwa Allah telah berketetapan untuk membinasakan penduduk Sodom dan Gomora, namun Abraham mencoba upaya bernegosiasi dengan Allah agar sekiranya mungkin Allah menjauhkan hukumanNya terhadap kota Sodom dan Gomora. Walaupun, pada kenyataannya yang selamat dari tragedi ini hanyalah Lot dan kedua anak perempuannya. Penelitian ini bermaksud membingkai kisah syafaat Abraham ini dari perspektif spritualitas Pentakostal. Dengan menggunakan metode tafsir naratif dan kajian literatur diharapkan bisa memberikan ulasan yang jelas tentang kehidupan yang dijalani oleh Abraham, memberikan makna yang kuat tentang syafaat Abraham, dan membingkainya dari perspektif spritualitas Pentakostal. Disimpulkan, kaum Pentakostal memandang bahwa kisah syafaat Abraham merupakan kisah tentang ketekunan iman, keberanian untuk bertindak karena belas kasihan terhadap sesama, serta merupakan gambaran misi gereja yang diberdayakan Roh Kudus.